Internalisasi Nilai Islam di era Post-truth: Instagram dr@zaidulakbar sebagai Media Literasi Informasi Kesehatan - Ditha Prasanti (Al-Izzah: Jurnal Hasil-Hasil Penelitian, 2020)
Author explains Instagram account about Islamic and health information. In the current post-truth era, when a variety of health information that is spread is not necessarily true, it can be justified or assumed to be true, the account of dr@zaidulakbar is present to counter the issue of health hoaxes. The author wants to know the process of internalizing Islamic values in the post-truth era through the account of dr@zaidulakbar as a media for literacy in health information. How not, as a doctor, his name became a credible source by carrying the mission of his mission in spreading health information to the public. The Instagram account has 2.1 million followers with a tagline that "goes back to the health of the al-Qur’an and the Sunnah of the Prophet Muhammad and His world". The author examines this research using virtual ethnographic methods, and data collection techniques such as observation, interviews, and literature studies. The results showed that 1) the process of internalizing Islamic values begins with verbal messages in the form of various health information based on the al-Qur’an and the Sunnah of the Apostles uploaded by ZA in his account and non-verbal messages carried by the account of dr@zaidulakbar; 2) dr@zaidulakbar's account is a solutive media in the process of internalizing Islamic values for millennial generation in the post-truth era; 3) dr@zaidulakbar's account responds to the challenges of the post-truth era as a medium for literacy in health information in minimizing health hoaxes.